ANALISIS MANAJEMEN RISIKO TERHADAP KINERJA KEUANGAN PERUSAHAAN DI BURSA EFEK INDONESIA - Kenamon, Mardiah; Dewi , Rosmala; Herlina, Tati; Rabiulkhri, Mailani; Meilani Siska, Wenny (Jurnal Bisnis Darmajaya, 2026)
The COVID-19 epidemic has resulted in elevated non-performing loan (NPL) levels at several banks in Indonesia, underscoring difficulties in executing risk management. The escalation of credit, liquidity, and operational risks during the crisis may impair banks' financial performance and jeopardize their stability and profitability. This study analyzes the effects of different risk management strategies on the stability and profitability of banks. This research seeks to assess the impact of liquidity risk, credit risk, and operational risk on financial performance, quantified by Return on Assets (ROA). A purposive sample strategy was employed, using eight banks and forty quantitative observations. The sample was established by a purposive sampling method, yielding eight banks with a cumulative total of 40 observations. The data sources were yearly reports and financial statements obtained from the official IDX website. Secondary financial statement data were examined by multiple linear regression analysis. The findings demonstrate that operational risk exerts no meaningful partial impact on financial performance, credit risk has a substantial negative effect, and liquidity risk has a considerable positive effect. These hazards substantially affect financial performance. This study indicates that sustaining bank stability and profitability in the face of regulatory and economic constraints necessitates effective and cohesive risk management.   Keywords: financial performance, operational risk, credit risk, liquidity risk, and risk management.